The Gist of Instructional Leadership Practised in Swaziland Primary Schools. (October 2016) - van der Merwe, Hettie; Schenck, Catherina
A growing body of scholarship links instructional leadership to effective teaching and learning. This article looks at the 'what' of instructional leadership as practised in Swaziland primary schools. A qualitative investigation was undertaken based on individual and focus group interviews conducted at eight primary schools in the Hhohho region of Swaziland. The findings show that demonstrative leadership accompanied by collaborative support and recognition for achievement are important features of an effective instructional leadership programme. The main limitations to optimal learning are the collection of school fees during school hours and balancing English as the language of instruction with preserving the indigenous language. The findings emphasize the importance of mutual effort as the main component of effective teaching and learning.